Pemanfaatan Container Menjadi Ruang Isolasi Apung Sebagai Alternatif Bagi Pasien Covid-19 - Lazuardi, Siti Dwi; Muaz, Akhdan Muhammad; Zahroh, Dina Fatimatuz; Airlangga, Altalariq Pranantha Yudha; Saputri, Afyfah Ramadhani Dias (Syntax Idea, 2021)
Until now, COVID-19 cases continue to increase, too many patients needing intensive care resulting in hospitals experiencing overloaded capacity conditions. In order to minimize the presence of independent care patients and the risk of family clusters, the use of containers becomes a floating isolation room as an alternative for the community to receive intensive COVID-19 treatment. Utilization of used 20 feet container combined with a base for floating made from HDPE (High-Density Polyethylene) and WPC (Wood Plastic Composite) footing. In considering the amount of costs and measuring the optimization of the benefits of the research, this research uses the CBA (Cost-Benefit Analysis) method and the BCR (Benefit Cost Ratio) method to test the feasibility of this research. The results showed that the use of used containers to be a floating isolation room was in the good category, where this study can reduce the number of self-isolating patients by 35% and the results of the calculation of the benefits have a ratio of 1.02 and produce a positive NPV value with eligibility limits, namely BCR> 1, and NPV> 1. From these results, it can be concluded that this floating isolation room is feasible to be realized or operated.